ANALISIS RISIKO ERGONOMI POSTUR KERJA KARYAWAN DENGAN METODE REBA DAN NBM DI PT. MMZ - Meri, Mufrida; Linda, Rozza; Risky, Ari (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Intensive manual handling activities in the spice processing industry often lead to musculoskeletal complaints among workers. This study aims to analyze the working posture of employees at the cinnamon wood unloading station at PT. MMZ using the Rapid Entire Body Assessment (REBA) and Nordic Body Map (NBM) methods. The REBA method is used to assess posture-related risk and provide improvement recommendations, while the NBM method identifies body parts experiencing discomfort. The results of the study indicate that the majority of workers fall into the high-risk category based on REBA analysis, with non-ergonomic postures such as bending, twisting the body, and lifting heavy loads being the main contributing factors. Additionally, the NBM findings show that most workers experience discomfort in the neck, shoulders, back, and waist. The conclusion of this study highlights the importance of ergonomic posture adjustments to reduce the risk of musculoskeletal injuries and improve worker well-being. Keyword: Working Posture; Musculoskeletal; REBA; NBM; Ergonomics. Abstrak: Kegiatan manual handling yang intens di industri pengolahan rempah-rempah sering kali menyebabkan keluhan muskuloskeletal pada pekerja. Penelitian ini bertujuan untuk menganalisis postur kerja karyawan di stasiun pembongkaran kayu kulit manis di PT. MMZ menggunakan metode Rapid Entire Body Assessment (REBA) dan Nordic Body Map (NBM). Metode REBA digunakan untuk menilai risiko postur kerja dan memberikan rekomendasi perbaikan, sedangkan metode NBM digunakan untuk mengidentifikasi bagian tubuh yang mengalami keluhan. Hasil penelitian menunjukkan bahwa mayoritas pekerja berada dalam kategori risiko tinggi berdasarkan analisis REBA, dengan postur kerja yang tidak ergonomis seperti membungkuk, memutar tubuh, dan mengangkat beban berat menjadi faktor utama. Selain itu, hasil NBM menunjukkan bahwa sebagian besar pekerja mengalami keluhan pada leher, bahu, punggung, dan pinggang. Kesimpulan dari penelitian ini menegaskan pentingnya penyesuaian postur kerja yang ergonomis untuk mengurangi risiko cedera muskuloskeletal dan meningkatkan kesejahteraan pekerja. Kata kunci: Postur Kerja; Muskuloskeletal; REBA; NBM; Ergonomi.